Model Pendampingan Koperasi Dalam Upaya Akselerasi Pencapaian Koperasi Modern - Restiany, Devi; Irawan, Dandan; Supriyadi, Deddy; Riyadhi Prayanda, Ibnu (Universitas Koperasi Indonesia, 2024)
Intervention efforts in dealing with the problems of modern cooperatives focus on priority needs, and one method is through assistance programs. This need includes experts as accompanying staff who can directly support cooperative management in overcoming obstacles or constraints that may arise in institutional development and cooperative business. This research aims to find the modern cooperative assistance program model in 2023. This research uses qualitative methods with data collection techniques in the form of interviews, document analysis, observation, and triangulation. The results show that the 2023 modern cooperative assistance program is